Constrained connection for distributed generation by DSOs in European countries - Ken Furusawa; Gert Brunekreeft; Toru Hattori (Jacobs University Bremen, Bremen Energy Research (BER), 2019)
A high penetration of renewable energy sources (RES) connected to the distribution network due to Feed-in-Tariff (FIT) brought many challenges for DSOs. With the responsibility to connect, DSOs may be required to make investment in the network. In order to connect distributed generation (DG) while deferring the investment, European DSOs use "constrained connection" by which DG is connected conditional on the curtailment. Different approaches for constrained connection in Europe exist and case studies of the different approaches in Germany, France, and UK show that the relative acceptability of DG and ease of curtailment by DSOs are different, depending on the energy policy background and technology available in each country.
Keywords: 330